PERAN JAMAâAH TABLIGH DALAM PEMBINAAN PENDIDIKAN AGAMA ISLAM PADA MASYARAKAT DESA TEMBORO KARAS MAGETAN - Romlah, Futiati (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
There are a number of religious guidance succeeded in building a good personality and character of Muslim conducted by a group or any particular religious stream. For instance, one of the groups is Jamaâah Tabligh of Temboro, Karas, Magetan. In line with this, it is necessary to learn in depth about this sort of group which is focused on the following issues: (1) the coaching forms of religious education and (2) the religious practice of the communities.Â  This study employed a qualitative descriptive approach through observation, interviews, and recording data as instruments. The results reveal that (1) the forms of religious education development are: (a) the activities of mosque community followed by elder and young men in the form of ubudiyah (call for prayer and congregation pray), daily meetings, hospitality, religious learning, lailatul ijtimaâ, maqomy recitation, and khuruj, (b) the activities of masturah followed by women and female teenagers involve religious family learning, weekly study groups, selapanan recitation, and three days out learning, and (c) Madrasah diniyah and tahfidzul Qurâan held by the community around the mosque without considering any age limitation, (2) The successful of religious education development isÂ  reflected on the high awareness of the society, for instance to: (a) do daily worship, (b) prosper the mosque to worship and other activities, (c) educate the children with Islamic education and (d) use Islamic clothes.Â ÙØ¬Ø ÙØ«ÙØ± ÙÙ Ø§ÙØ¬ÙØ§Ø¹Ø§Øª Ø£Ù Ø§ÙÙØ±Ù Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙ ØªØ±Ø¨ÙØ© Ø§ÙÙØ§Ø³ Ø§ÙÙÙØªÙÙÙ Ø¥ÙÙÙØ§ ØªØ±Ø¨ÙØ© Ø¥Ø³ÙØ§ÙÙØ©Ø ÙÙÙ ÙØ°Ù Ø§ÙØ¬ÙØ§Ø¹Ø§Øª " Ø¬ÙØ§Ø¹Ø© Ø§ÙØªØ¨ÙÙØº" ÙÙ ØªÙØ¨ÙØ±Ù ÙØ§Ø±Ø³ ÙØ§ØºØªØ§Ù . Ø£Ø±Ø§Ø¯ Ø§ÙØ¨Ø§ØØ« Ø¯Ø±Ø§Ø³Ø© ÙØ°Ù Ø§ÙØ¬ÙØ§Ø¹Ø© Ø¹ÙÙÙØ©. ÙØªÙÙÙ Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ ÙÙØ·ØªÙÙ Ø£Ø³Ø§Ø³ÙØªÙÙ : ÙÙØ§ (Ø£) ØµÙØ± Ø¹ÙÙÙØ© ÙÙØªØ±Ø¨ÙØ© Ø§ÙØ¯ÙÙÙØ© (Ø¨) ØªØ·Ø¨ÙÙ Ø§ÙØ¹Ø¨Ø§Ø¯Ø§Øª ÙØ§ÙØ´Ø¹Ø§Ø¦Ø± Ø§ÙØ¯ÙÙÙØ©. ÙØ¨Ø£Ø³ÙÙØ¨ Ø§ÙÙÙØ§ØØ¸Ø© ÙØ§ÙÙÙØ§Ø¨ÙØ© ÙØ§ÙÙØ¯Ø®Ù Ø§ÙÙØµÙÙ Ø§ÙÙÙÙÙ ØØµÙ Ø§ÙØ¨Ø§ØØ« Ø¹ÙÙ Ø§ÙÙØªØ§Ø¦Ø¬ Ø§ÙØªØ§ÙÙØ©: (Ø£) Ø¥Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¯ÙÙÙØ© Ø§ÙØªÙ ÙØ§Ù Ø¨ÙØ§ " Ø¬ÙØ§Ø¹Ø© Ø§ÙØªØ¨ÙÙØº " ÙÙ (1) ØªØ·Ø¨ÙÙ ØµÙØ§Ø©Â  Ø§ÙØ¬ÙØ§Ø¹Ø© ÙÙ Ø§ÙÙØ³Ø¬Ø¯Ø ÙØ´ØªØ±Ù ÙÙÙØ§ Ø§ÙØ£Ø¨Ø§Ø¡ ÙØ§ÙØ£ÙÙØ§Øª ÙØ§ÙØ´Ø¨Ø§Ù ÙØ§ÙØ´Ø§Ø¨Ø§Øª Ù ØµÙØ© Ø§ÙØ±ØÙ ÙØ§ÙØ´ÙØ±Ù ÙØ§ÙØªØ¹ÙÙÙ Ø§ÙÙÙÙÙ Ù Ø§ÙØ´ÙØ±Ù (2) ÙØ´Ø§Ø· " Ø§ÙÙØ³ØªÙØ±Ø© " Ø§Ø´ØªØ±Ù ÙÙÙØ§ Ø§ÙØ´Ø¨Ø§Ù ÙØ§ÙØ´Ø§Ø¨Ø§Øª Ø ÙÙÙÙ ØªØ¹ÙÙÙ Ø¯ÙÙÙ Ø£Ø³Ø±ÙØ ÙØªØ¹ÙÙÙ Ø£Ø³Ø¨ÙØ¹ÙÙ Ø ÙØªØ¹ÙÙÙ Ø´ÙØ±ÙÙ Ù Ø§Ø±Ø³Ø§Ù Ø§ÙØ¯Ø¹Ø§Ø© ÙÙØ¯Ø© 3 Ø£ÙØ§Ù (2) Ø§ÙÙØØ§Ø¶Ø±Ø© Ø§ÙØ¹Ø§ÙØ© Ù ØªØÙÙØ¸ Ø§ÙÙØ±Ø§Ù. Ø§Ø´ØªØ±Ù ÙÙÙØ§ Ø§ÙÙØ¬ØªÙØ¹ Ø¹Ø§ÙØ© (Ø¨) ÙØ¬Ø§Ø ÙØ°Ù Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ÙØ£ÙØ´Ø·Ø© Ø§ÙØ¯ÙÙÙØ© ØªØ¸ÙØ± ÙÙ ÙØ¹Ù Ø§ÙÙØ¬ØªÙØ¹ (1) ÙØ£Ø¯Ø§Ø¡ Ø§ÙØ¹Ø¨Ø§Ø¯Ø§Øª ÙÙÙÙØ§ (2) ÙØ¹ÙØ§Ø±Ø© Ø§ÙÙØ³Ø§Ø¬Ø¯ Ø¨Ø§ÙØ¹Ø¨Ø§Ø¯Ø§Øª ÙØºÙØ±ÙØ§ (3) ØªØ±Ø¨ÙØ© Ø§ÙØ£ÙÙØ§Ø¯ ØªØ±Ø¨ÙØ© Ø¥Ø³ÙØ§ÙÙØ© (5) ÙØ§ÙØ§Ø±ØªØ¯Ø§Ø¡ Ø¨ÙØ¨Ø§Ø³ Ø¥Ø³ÙØ§ÙÙ.Â